Resistencia al aplastamiento de pernos de acero en cuerpos de prueba de madera de acuerdo con las normas técnicas ABNT NBR 7190:1997 y ASTM D5764:2007 - Molina, Julio Cesar [UNESP]; Rodrigues De Oliveira, Diego [UNESP]; Negreli, Murilo [UNESP]; Friedmann Pallarolas, Ernesto Abel Fernando [UNESP] (My University, 2017)
The aim of this work was the study of embedment strength of dowels in reforested wood pieces. Analytical and experimental approaches were considered. Specimens for testing were made of Pinus elliottii (C30) and Eucalyptus saligna (C50) wood with steel rods with diameter of 6.35 mm (1/4”). The tests were performed according to the recommendations of ABNT NBR 7190:1997 and ASTM D5764:2007 Standards with subsequent comparison between the analytical and experimental results for embedment strength in the parallel and perpendicular directions to the grain. The results showed that the analytical and experimental values for embedment strength according to American Standard presented closer to each other compared to the Brazilian Standard in this case. Moreover, the American Standard recommended test specimen dimensions, which facilitate the manufacture, especially in the direction perpendicular the to wood fibers.
Embedment strength of steel dowel in wood specimens according to ABNT NBR 7190:1997 and ASTM d5764: 2007 standards
Keywords: Analytical models; Experimental tests; Standardization